Peran Guru Dalam Memberikan Bimbingan Belajar Untuk Mengatasi Kesulitan Membaca Siswa Kelas 3 DI SDN Cangkol 3 Tahun Ajaran 2016/2017 - Saputro, Wahid Imam, Drs. Saring Marsudi, SH. M.Pd (2017)
This research is intended for several things in Class 3 SDN Cangkol 3, among others: 1) Characteristics of students who have difficulty reading, 2) The role of teachers to overcome reading difficulties, 3) Form of Tutoring provided by teachers to overcome reading difficulties, 4) Barriers Experienced by teachers to overcome reading difficulties, 5) Solutions given by teachers to overcome reading difficulties. This type of research is qualitative and the research design is descriptive research. Informants in this research are 3rd graders and four students who have difficulty reading. Technical data using observation, interview and documentation. The validity of the data using tri sources and methods. The results showed: 1) Characteristics of students who have difficulty reading one with the others vary so that teachers should help each other in accordance with their respective needs, 2) The role of teachers in overcoming students who have difficulty reading, that is giving advice, motivation And accompany Students who have difficulty reading by giving special attention, 3) the form of learning guidance done in overcoming students who have difficulty reading teaching method, early reading method, the use of book fairy tale or story and strategy of language experience, 4) The deep barriers Provide tutoring , There is no awareness from within the students themselves to practice reading, the students themselves do not pay attention to teacher explanations, and the attention of parents, 5) solution in overcoming barriers to reading, so hostility Class Agar conducive and participate to accompany children while studying at home. Keywords: Teacher Role, Tutoring, Reading Difficulty